Taxonomia e biogeografia da espécie politípica Herpsilochmus rufimarginatus (TEMMINCK, 1822) (Aves: THAMNOPHILIDAE) - Silva, Marcelo da (2013)
The genus Herpsilochmus is composed mainly of cryptic species, among them is Herpsilochmus rufimarginatus, which is currently represented by four subspecies: H. r. rufimarginatus, H. r. frater, H. r. scapularis and H. r. exiguus. Differences in plumage and vocalization suggest that there are more than one species involved in this complex. Thus this and other subspecific taxa need urgent revision, the disjunct distribution of this species also allows us to infer the relationship between birds that occur in this biome and / or different centers of endemism. This study aims to make a taxonomic revision of the taxa included in the complex time Herpsilochmus rufimarginatus based on morphological, morphometric, vocals and geographical distribution of this bird. Besides creating distribution models current potential and make the reconstruction of the distribution bygone using ecological niche modeling, and testing the niche conservatism and divergence between different subspecies. Consultations for examination of the skins of specimens of the museums: Museum of Zoology, University of São Paulo (MZUSP), National Museum of Rio de Janeiro (MN) and Emilio Goeldi Museum of Pará (MPEG), and the skins deposited at the collection of Ornithological Federal University of Rio Grande do Norte (COUFRN). We studied the following measures length of specimens: exposed culmen, culmen and total culmen nostril, tarsus, wing and tail flattened. The voice analysis was performed with vocalizations banks and / or digital banks people where 17 voice parameters were measured. This information and more available in the literature were used to assemble a bunch of data under the limit distribution of taxa and generate ecological niche models. This analyzes carried out in the program Maxent, having as model selection criterion the AUC, and the models were greater than 0.80 are considered good models. Environmental data for the realization of the modeling were downloaded on the website of Worldclim. The morphometric information, vocals and geographic distribution point for the separation of these taxa to be considering various uni and multivariate analyzes. The potential distribution models performed well (AUC> 0.80), and its distribution associated with environmental characteristics of the Amazon forest and Atlantic forest (forests of south and southeast, northeast and forest). The reconstruction of the distribution indicates a possible contact between the southern part of the Atlantic forest in the northern part of the Amazon. The analysis of niche overlap showed a low overlap between taxa and comparisons between the null model and the generated overlay link probably occurring niche conservatism. The data suggest that the taxa that occur in the Amazon and Atlantic forest represent three distinct species